COMPARISON OF THE SOIL DEFORMATION MODULUS VALUES RECEIVED BY THE LABORATORY AND IN SITU TESTS RESULTS - Poklonskyi, S. V.; Korniyenko, M. V. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The soil deformation modulus largely depends on the obtaining method. There are various methods of determining E. In compression soil test a ring of small size is used. It causes a number of factors affecting the test results. The comparison of deformation modulus values obtained by in situ and laboratory methods is shown in article. It was believed for a long time that the oedometer deformation modulus of sands practically does not differ from the plate deformation test modulus, and therefore no transitional coefficients for this soil are given. However, it has been experimentally established that the results of oedometer tests of sands need to be corrected.